2016
DOI: 10.3390/nu8110719
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Cellular and Metabolic Responses of World-Class Canoeists Training: A Sportomics Approach

Abstract: (1) Background: We have been using the Sportomics approach to evaluate biochemical and hematological changes in response to exercise. The aim of this study was to evaluate the metabolic and hematologic responses of world-class canoeists during a training session; (2) Methods: Blood samples were taken at different points and analyzed for their hematological properties, activities of selected enzymes, hormones, and metabolites; (3) Results: Muscle stress biomarkers were elevated in response to exercise which cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 81 publications
0
11
0
1
Order By: Relevance
“…While short-term metabolite changes after one exercise session in athletes were reported (Al-Khelaifi et al, 2018, 2019Breit et al, 2015;Coelho et al, 2016;Hall et al, 2016;Howe et al, 2018), no study showed how years of metabolic adaptation to endurance, resistance, or sprint training affect metabolite changes to the same acute exercise.…”
Section: Introductionmentioning
confidence: 99%
“…While short-term metabolite changes after one exercise session in athletes were reported (Al-Khelaifi et al, 2018, 2019Breit et al, 2015;Coelho et al, 2016;Hall et al, 2016;Howe et al, 2018), no study showed how years of metabolic adaptation to endurance, resistance, or sprint training affect metabolite changes to the same acute exercise.…”
Section: Introductionmentioning
confidence: 99%
“…This fact should be considered when prescribing physical training strategies, which should be based on parameters presented by specific studies. In this regard, studies with sports methods have emerged in recent decades as an ideal strategy to study the interactions between exercise, the immune system, and metabolism via cellular adaptations (Bassini-cameron, Bottino, Bittar, Veiga, & Cameron, 2007;Bessa et al, 2008;Coelho et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Taking the scientific achievements, and available sports infrastructure into account, it is necessary to improve the recommendations made to young athletes for the early detection of a predisposition to engage in specific sports by using physiological, medico-biochemical, and molecular genetic methods. Today, the global scientific community is actively working to identify the endogenous molecular factors and processes that can act as personalized predictors of athletic performance [10][11][12].…”
Section: Introductionmentioning
confidence: 99%